Welfare Quality® project: from scientific research to on farm assessment of animal welfare - Linda Keeling; Elisabetta Canali (Italian Journal of Animal Science, 2010)
Welfare Quality® is the acronym of the European research project “Integration of ani- mal welfare in the food quality chain: from public concern to improved welfare and transparent quality”. This European project is focused on the integration of animal welfare in the food quality chain. Italian researchers from University of Milan, Naples, Padua, Parma and Pisa are involved in different tasks of this project. The second sub-project of Welfare Quality® aims to develop assessment systems to evaluate and monitor the quality of animal welfare on farms or at slaughter in 7 livestock species. Researchersof Researchers of the Department of Animal Science of the University of Milan worked together other European partners to find and develop the most suitable animal-based measures for dairy and beef cattle.